Pengukuran Produktivitas Karyawan Dengan Metode Full Time Equivalent (FTE) PT. Astra International Tbk Divisi Astra Motor Penempatan Jakarta Honda Center - Gidion Karo Karo; Erwin Adianto (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
Nowadays so many of the problems faced by the products and services company where competition is getting tougher. The longer the running time is also a growing consumer desire both product and service specifications. When consumers want products with good quality industry players must further develop ways to optimize production costs ntuk maximum results. One method used is to increase employee productivity. Employee productivity is seen as one of the determining factors that will affect the output of the company's products or services. Basically, productivity can be seen from the amount of output produced in a given time period and calculate a percentage. Employees who have a fast output can be categorized not necessarily productive or otherwise. In this observation reports used method, wherein a Full-Time Equivalent calculation result will be a valid number that describes a specific period, which will be seen from this figure whether or not the employee is a productive enterprise and a reference to add, subtract, and corrects the job description and workflow that exist within the company. The observations can also find some of the findings of the field which is also a reference company to make improvements and changes to systems and facilities.Keywords: Full-Time Equivalent, Employee Productivity